PLEISTOCENE PALAEOCLIMATIC EVOLUTION FROM AGIOS GEORGIOS CAVE SPELEOTHEM (KILKIS, N. GREECE) - Dotsika, E.; Psomiadis, D.; Zanchetta, D.; Spyropoulos, N.; Leone, G.; Tzavidopoulos, I.; Poutoukis, D. (Bulletin of the Geological Society of Greece, 2010)
Palaeoclimatic reconstruction in N. Greece has been investigated in this study, using stable isotope analyses and U/Th dating of a speleothem (stalactite) from the cave of Agios Georgios (Kilkis). Sampling sequence was followed in detail in order to obtain high resolution analysis of the proxy. Speleothem δ18O entirely depends on two factors: changes in the δ18O of the percolation waters (a proxy for local rainfall δ18O) and the temperature of water-calcite fractionation inside the cave (a proxy for outside air temperatures). During periods of relatively stable temperatures, δ13C shifts are caused principally by variations in soil CO2 input and physico-chemical processes inside the cave. More important processes affect the δ13C signal of speleothem inside the cave are length of flow path and rates of CO2 degassing.The lower δ13C calcite values indicate greater respiratory activity of soils under wetter conditions. The stalagmite layers were dated through U/Th geochronological method, which places the carbonate precipitation in Middle Pleistocene (630-300ka BP). The isotopic composition of the layers was used in combination with the dating results to reconstruct the evolution of the area of Kilkis. Correlation with global climatic records shows that major climatic transitions that influenced northern hemisphere seem to have also affected the region of N. Greece.